Faktor-faktor yang Memengaruhi Persepsi Negatif Petani dan Identifikasi Tutupnya Lembaga Permodalan di Desa Koripan, Kecamatan Matesih, Kabupaten Karanganyar - Dunya, Phiera Aura Kartika; Prayoga, Kadhung; Mariyono, Joko (Universitas Galuh, 2025)
Perception is the stage where information enters a person's mind and is associated with their thoughts, emotions, and individual experiences. Farmers' perceptions of financial institutions reflect their expectations, yet many feel doubtful or hold negative views. This research aims to analyze farmers' negative perceptions of financial institutions and identify the causes of their closure. The study was conducted from June to August 2024 in Koripan Village, Matesih Subdistrict, Karanganyar Regency. The survey method was used in this research. The sampling method applied was proportionate random sampling using Isaac and Michael's formula, with a total sample of 257 farmers, and purposive sampling for selecting the sample from the financial institution's management. Data were analyzed using multiple linear regression to determine the factors influencing farmers' perceptions, score intervals to categorize the level of negative perception, and descriptive analysis to identify the causes of the institutions' closure. The results of this study show that all independent variables significantly affect farmers' negative perceptions both simultaneously and partially, leading to the closure of financial institutions due to internal and external factors. Distrust, bad experiences, skepticism, and low expectations lead farmers to prefer old practices, even if they are no longer optimal. In the future, financial institutions should conduct widespread socialization, have their management directly supervised by the government, and regenerate members with sufficient financial management skills.